The Association Between Parity and Cervical Cancer Risk: A Systematic Review - Bangar Parlinggoman Tua; Yahya Nurlianto; Mutia Juliana (The International Journal of Medical Science and Health Research, 2025)
Introduction: Cervical cancer remains the fourth most common cancer in women globally (Sung et al., 2021; World Health Organization, 2024). While persistent infection with high-risk human papillomavirus (HPV) is established as the necessary cause, it is insufficient for carcinogenesis (Walboomers et al., 1999). Parity (the number of live births) has long been suspected as a critical cofactor, but evidence has been inconsistent (Tekalegn et al., 2022). This review synthesizes the epidemiological evidence on this association. Methods: This systematic review was conducted adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines (Page et al., 2021). A systematic search of MEDLINE/PubMed, Scopus, HINARI, Google Scholar, and Science Direct was performed (Tekalegn et al., 2022). Inclusion criteria were case-control or cohort studies quantifying the association between parity and cervical cancer risk. The methodological quality of included studies was assessed using the Newcastle-Ottawa Scale (NOS) (Wells et al., 2000). Results: A total of 18 observational studies, comprising 17 case-control studies and one prospective cohort study, were included in the final synthesis. A recent, high-quality meta-analysis incorporating many of these studies (Tekalegn et al., 2022) reported a significant pooled odds ratio (OR) from 6,685 participants. The analysis showed that women with high parity had 2.65 times higher odds of developing cervical cancer compared to their low-parity counterparts (OR = 2.65, 95% CI: 2.08–3.38). This review confirms this finding and further highlights a significant dose-response relationship, with risk increasing progressively with each additional birth (Muñoz et al., 2002; Sharma and Pattanshetty, 2018). Discussion: The evidence confirms that high parity is a major, independent cofactor that promotes carcinogenesis, particularly in HPV-positive women (Muñoz et al., 2002). This association is not an artifact of confounding by sexual behavior. Proposed biological mechanisms include: (1) supraphysiological hormonal changes during pregnancy promoting HPV oncogene expression; (2) persistent eversion (ectropion) of the cervical transformation zone, increasing epithelial vulnerability (Jensen et al., 2013); (3) cervical trauma during childbirth facilitating viral persistence; and (4) localized, pregnancy-related immunomodulation that impairs viral clearance. Conclusion: High parity is a robust and significant risk factor for cervical cancer. This finding has direct implications for public health, identifying women with high parity as a high-risk group that should be prioritized for cervical screening and HPV vaccination programs, especially in resource-limited settings where both high parity and cervical cancer incidence are prevalent.